An overview of the geology and production of the Fuling shale gas field, Sichuan Basin, China - Nie, Haikuan; Li, Donghui; Liu, Guangxiang; Lu, Zhiyuan; Hu, Wang; Wang, Ruyue; Zhang, Guangrong (Energy Geoscience, 2020)
The Fuling shale gas field in China is the largest shale gas field as well as the largest of its type discovered in any Lower Paleozoic formation. In this study, the geology and production of the upper and lower gas layers in the Fuling shale gas field are evaluated in terms of structure, shale quality, fault, initial production, and estimated ultimate recovery (EUR). The shale in the lower gas layer of the Jiaoshiba anticline is a high-quality reservoir, where the space is dominated by organic pores in kerogen, and the gas content is high. The shale gas wells reveal relatively high initial production and EUR. However, the shale in the upper gas layer of the Jiaoshiba anticline has reservoir space mainly composed of clay mineral pores and organic pores within bitumen, and the gas content is low. In terms of structure, primary gas migration may occur in the upper gas layer, resulting in free gas accumulation in the structural high, where the development effects are generally better than those in the structural low. The lower gas layer in the Pingqiao anticline, is the main interval for shale gas accumulation and development due to the high-quality shale. Under the influence of faults, the efficiency of exploration wells emplaced on top of the anticline is much lower a compared with those in the flanks. The residual synclines close to the Sichuan Basin, including the Baima and Baitao anticlines, are characterized by more recent uplifts, larger area, greater distance from the deep and large faults, and early fracture closure. Therefore, we recommend that the shale gas exploration and development should be carried out preferentially in areas close to the center of the residual synclines, featuring relatively high-pressure coefficient and moderate burial depth. [Display omitted] •Geology and production of gas layers in the Jiaoshiba anticline.•Shale gas migration and accumulation in the structural high of the upper gas layer.•The residual synclines far away from the fault have high development potential.